MicroRNA treatment modulates osteogenic differentiation potential of mesenchymal stem cells derived from human chorion and placenta - Kulisara Marupanthorn (Nature Portfolio, 2021)
Abstract Mesenchymal stem cells (MSCs) are important in regenerative medicine because of their potential for multi-differentiation. Bone marrow, chorion and placenta have all been suggested as potential sources for clinical application. However, the osteogenic differentiation potential of MSCs derived from chorion or placenta is not very efficient. Bone morphogenetic protein-2 (BMP-2) plays an important role in bone development. Its effect on osteogenic augmentation has been addressed in several studies. Recent studies have also shown a relationship between miRNAs and osteogenesis. We hypothesized that miRNAs targeted to Runt-related transcription factor 2 (Runx-2), a major transcription factor of osteogenesis, are responsible for regulating the differentiation of MSCs into osteoblasts. This study examines the effect of BMP-2 on the osteogenic differentiation of MSCs isolated from chorion and placenta in comparison to bone marrow-derived MSCs and investigates the role of miRNAs in the osteogenic differentiation of MSCs from these sources. MSCs were isolated from human bone marrow, chorion and placenta. The osteogenic differentiation potential after BMP-2 treatment was examined using ALP staining, ALP activity assay, and osteogenic gene expression. Candidate miRNAs were selected and their expression levels during osteoblastic differentiation were examined using real-time RT-PCR. The role of these miRNAs in osteogenesis was investigated by transfection with specific miRNA inhibitors. The level of osteogenic differentiation was monitored after anti-miRNA treatment. MSCs isolated from chorion and placenta exhibited self-renewal capacity and multi-lineage differentiation potential similar to MSCs isolated from bone marrow. BMP-2 treated MSCs showed higher ALP levels and osteogenic gene expression compared to untreated MSCs. All investigated miRNAs (miR-31, miR-106a and miR148) were consistently downregulated during the process of osteogenic differentiation. After treatment with miRNA inhibitors, ALP activity and osteogenic gene expression increased over the time of osteogenic differentiation. BMP-2 has a positive effect on osteogenic differentiation of chorion- and placenta-derived MSCs. The inhibition of specific miRNAs enhanced the osteogenic differentiation capacity of various MSCs in culture and this strategy might be used to promote bone regeneration. However, further in vivo experiments are required to assess the validity of this approach.